Challenges collecting pro-WEAI data in climate-affected Nandi County, Kenya - Mwambi, Diana; Ewell, Hanna; Rietveld, Anne (2024)
The author narrates challenges encountered when leading a team of enumerators to collect data for the pro-WEIA index in Nandi county, Kenya